The refinements of some theorems for the random branching processes - Nagaev, A.; Badalbaev, I. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. В. Нагаев, И. Бадалбаев. Уточнение некоторых теорем о ветвящихся случайных процессах A. Nagajevas, I. Badalbajevas. Kai kurių teoremų apie išsišakojančius atsitiktinius procesus patikslinimus